No bees no honey: Apiculture value chain experiences in Ethiopia - International Livestock Research Institute (International Livestock Research Institute, 2012)
‘No bees no honey’ presents the experience of the Improving Productivity and Market Success (IPMS) project on apiculture value chain development in Bure distrct, Amhara, Ethiopia. IPMS together with the woreda office of agriculture, farmers, input suppliers and other stakeholders worked in the district to produce high quality honey by using integrated commodity development approach. On this video, all successive value addition activities and processes such as production, where queen splitting was a major intervention, input supply, and marketing interventions made by the project are highlighted.